Study of AC Utilization at some Departments in HCMUTE - Dang , Thành Trung (Journal of Technical Education Science, 2008)
More efficient use of energy will reduce fuel consumption and help improving the environment; it will not only help cost effectiveness, but also contribute substantially to improved prospects for the economy. Energy saving will reduce power pressure of the power source National Grid.